2017
DOI: 10.1364/oe.25.014227
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared surface plasmon resonance sensor based on photonic crystal fibers

Abstract: A surface plasmon resonance (SPR) sensor with two open-ring channels based on a photonic crystal fiber (PCF) is described. The sensor is designed to detect low refractive indexes between 1.23 and 1.29 with the operation wavelength in mid-infrared region between 2550 nm and 2900 nm. The coupling characteristics and sensing properties are numerically analyzed by the finite element method. The average spectral sensitivity is 5500 nm/RIU and a maximum resolution of 7.69 × 10 RIU can be obtained. Our analysis shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(69 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…For λ3, it is not difficult to see the interaction between the Au cube and SiO2 under the action of incident waves through Figure 4i. From Figure 4, it can be concluded that the surface plasmon polaritons' (SPPs) resonance and Fabry-Pero resonance show that there will be a strong electromagnetic field distribution near the nano scale groove [61][62][63]. In addition, in order to better understand the physical mechanism of peaks, we calculate the Figure 3a-c the corresponding electric diagram in the XOY plane.…”
Section: Refermentioning
confidence: 99%
“…For λ3, it is not difficult to see the interaction between the Au cube and SiO2 under the action of incident waves through Figure 4i. From Figure 4, it can be concluded that the surface plasmon polaritons' (SPPs) resonance and Fabry-Pero resonance show that there will be a strong electromagnetic field distribution near the nano scale groove [61][62][63]. In addition, in order to better understand the physical mechanism of peaks, we calculate the Figure 3a-c the corresponding electric diagram in the XOY plane.…”
Section: Refermentioning
confidence: 99%
“…air RI of the core-cladding was taken as = n 2 1 and = n 1.45 2 respectively. The dielectric constant of gold in the visible and near-IR region is defined by the Drude model described as [22]:…”
Section: Structure Design and Numerical Modelingmentioning
confidence: 99%
“…The application of levitated monolayer graphene in photovoltaic field is limited to some extent because its absorption efficiency of ordinary incident light is merely 2.3% [26]. All in all, resonance effect is the key method for enhancing material absorption or emission [27,28]. In the middle and far infrared bands, graphene has high plasma resonance, which is widely made use of enhancing the absorption efficiency of graphene.…”
Section: Introductionmentioning
confidence: 99%